2019
DOI: 10.1093/rheumatology/kez465
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of immune-mediated tissue lesions following treatment with immune checkpoint inhibitors

Abstract: Immune check point inhibitor (CPI) therapy has revolutionized treatment paradigms for several cancers, but at the cost of triggering a diverse spectrum of immune-mediated injury to non-cancer tissues. The complex biology of these toxicities remains incompletely understood, partly because tissue acquisition from affected areas can be challenging to retrieve, thus hindering development of targeted therapy. Here, we review the literature describing pathology of immune-mediated tissue lesions including gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 84 publications
0
31
0
1
Order By: Relevance
“…On the other hand, their increasing use has brought to attention numerous immune mediated side effects, little described until now, which can affect virtually any organ system. Some examples include enterocolitis, pneumonitis, hepatitis, hypophysitis, inflammatory arthritis, and a variety of skin manifestations [5]. With respect to the latter, they can further be categorized in four groups according to histological patterns: inflammatory, immunobullous, alteration of epidermal keratinocytes, and alteration of epidermal melanocytes, in which tumoral melanosis is included [5].…”
Section: Case Discussionmentioning
confidence: 99%
“…On the other hand, their increasing use has brought to attention numerous immune mediated side effects, little described until now, which can affect virtually any organ system. Some examples include enterocolitis, pneumonitis, hepatitis, hypophysitis, inflammatory arthritis, and a variety of skin manifestations [5]. With respect to the latter, they can further be categorized in four groups according to histological patterns: inflammatory, immunobullous, alteration of epidermal keratinocytes, and alteration of epidermal melanocytes, in which tumoral melanosis is included [5].…”
Section: Case Discussionmentioning
confidence: 99%
“…A retrospective study showed that the most common adverse events were colitis, hepatitis, adrenocorticotropic hormone insufficiency, and hypothyroidism, followed by type 1 diabetes, acute kidney injury, and myocarditis [ 64 ]. Skin, rheumatic toxicity and pneumonitis have also been reported [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that higher grade irAEs were observed when anti-PD-1 and anti-CTLA-4 were combined, similarly to patient responses to combination ICI therapy. Altogether, it is likely that the development of irAEs is a multifactorial process leading to patient-specific organ involvement [26].…”
Section: Discussionmentioning
confidence: 99%